Original paperEchocardiographic evaluation of myocardial strain in patients after transcatheter aortic valve implantation - Bochenek, Tomasz; Kusz, Blazej; Mizia, Magdalena; Lelek, Michal; Turski, Maciej; Wita, Krystian; Ochała, Andrzej; Mizia-Stec, Katarzyna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction: Echocardiographic evaluation of regional myocardial function helps to assess the efficacy of therapeutic interventions and to predict the prognosis and clinical outcomes. Aim: To assess whether myocardial strain can be useful in estimation of left ventricle (LV) function in patients who have undergone transcatheter aortic valve implantation (TAVI). Material and methods: Twenty-six patients with severe aortic stenosis, who successfully underwent TAVI, were enrolled in the study. Left ventricular peak systolic longitudinal strain (LV PSLS) was obtained before and 1 year after the procedure. Analysis included the potent influence of factors such as sex, LV ejection fraction (LVEF), type of prosthesis implanted or the type of the approach on LV PSLS values. Results: We observed a significant improvement in LV PSLS values after TAVI (–10.9 ±5.7 vs. –13.4 ±4.7, p < 0.05). Men had better improvement in LV PSLS after TAVI, but their starting values were considerably lower (M: –10.7 ±4.5 before vs. –13.3 ±4.9 after, p < 0.05; W: –11.8 ±6.8 before vs. –11.9 ±5.6 after, p = NS). Patients with starting LVEF ≤ 40% benefited from the procedure (LV PSLS: –10.3 ±6.4 before vs. –13.7 ±2.9 after, p < 0.05), but in the group of patients with the higher starting LVEF no significant changes in LV PSLS were observed. We also did not note any differences in LV PSLS depending on type of the prosthesis implemented (Edwards Sapiens/CoreValve). Patients in whom the prostheses were implemented via the femoral approach only presented significant increase in LV PSLS values (before: –10.4 ±6.7 vs. after: –13.6 ±3.7, p < 0.05). Conclusions: The TAVI results in improvement of LV systolic function according to LV PSLS values. Some factors, especially lower baseline LVEF, are related to increased benefit in LV PSLS after TAVI.